2015
DOI: 10.1128/jvi.00243-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Megabirnavirus from Sclerotinia sclerotiorum Reveals Horizontal Gene Transfer from Single-Stranded RNA Virus to Double-Stranded RNA Virus

Abstract: Mycoviruses have been detected in all major groups of filamentous fungi, and their study represents an important branch of virology. Here, we characterized a novel double-stranded RNA (dsRNA) mycovirus, Sclerotinia sclerotiorum megabirnavirus 1 (SsMBV1), in an apparently hypovirulent strain (SX466) of Sclerotinia sclerotiorum. Two similarly sized dsRNA segments (L1-and L2-dsRNA), the genome of SsMBV1, are packaged in rigid spherical particles purified from strain SX466. The full-length cDNA sequence of L1-dsRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…A). All field isolates of megabirnaviruses carry two genomic dsRNA segments (Chiba et al ., ; Nerva et al ., ; Sasaki et al ., ; Wang et al ., ), except for a megabirna‐related dsRNA virus (Rhizoctonia solani RNA virus HN008), whose genome is assumed to be an undivided dsRNA (Zhong et al ., ). Only dsRNA 1 of RnMBV3 was sequenced and no contigs were obtained from dsRNA 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A). All field isolates of megabirnaviruses carry two genomic dsRNA segments (Chiba et al ., ; Nerva et al ., ; Sasaki et al ., ; Wang et al ., ), except for a megabirna‐related dsRNA virus (Rhizoctonia solani RNA virus HN008), whose genome is assumed to be an undivided dsRNA (Zhong et al ., ). Only dsRNA 1 of RnMBV3 was sequenced and no contigs were obtained from dsRNA 2.…”
Section: Resultsmentioning
confidence: 99%
“…This homologous region of PgLV1, except for the 2A‐like peptide motif, does not show any sequence similarity to other related hypoviruses such as FpHV1. These strongly suggest HGT between a (+)ssRNA virus (RnHV1) and a dsRNA virus (phlegiviruses), as in the case for the Phytoreo_S7 domain (Liu et al ., ; Hisano et al ., ) and papain‐like cysteine protease (Wang et al ., ). Likewise, the well‐conserved 2A‐like motif of yadokariviruses (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, because they are the primary inoculum source for disease epidemiology, this deficiency might be harmful for pathogen spread but favor the control of this pathogen. Interactions between some hypovirulence-associated viruses and their hosts have contributed to the establishment of some host-mycovirus systems, by which we can better understand the molecular basis of fungal biology, especially for fungal pathogenesis (Xie and Jiang, 2014; Wang et al, 2015). These host-mycovirus systems, including Cryphonectria parasitica-hypovirus (Nuss, 1996, 2011; Dawe and Nuss, 2001, 2013; Hillman and Suzuki, 2004; Milgroom and Cortesi, 2004; Nuss, 2005; Pearson et al, 2009), Helmintosporium victoriae-HvV190S (Li H. et al, 2011; Dunn et al, 2013; Ghabrial et al, 2013), Sclerotinia sclerotiorum-mycovirus (Li et al, 2008), Rosellinia necatrix-mycovirus (Salaipeth et al, 2013; Yaegashi et al, 2013), and Fusarium graminearum-mycovirus (Kwon et al, 2009; Cho et al, 2012), have been established and thoroughly elucidated, providing plenty of references to study fungal pathogenicity (Xie and Jiang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their potential use in biological control, studying the phenomenon of mycovirus-mediated hypovirulence is attractive for numerous researchers. In addition, the hypovirulence-associated mycoviruses, which have divergent molecular characteristics, will also enhance our understanding of virus diversity and evolution and contribute to the establishment of host-mycovirus systems (i.e., Cryphonectria parasitica-hypovirus, Helmintosporium victoriae-HvV190S, Sclerotinia sclerotiorum-mycovirus, Rosellinia necatrix-mycovirus, and Fusarium graminearum- mycovirus), which are beneficial for studying virus-host interactions including fungal and viral pathogenesis at the molecular level (Xie and Jiang, 2014; Wang et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mycoviruses could potentially be explored to control human fungal diseases (6). Mycoviruses are also very important toward an understanding of the diversity, evolution, and ecology of viruses; they are often found to be phylogenetically related to plant and animal viruses (7,8), and some newly discovered mycoviruses showed linkages between dsRNA and ssRNA viruses (9)(10)(11). Chiba and Suzuki found that one mycovirus could interfere with the replication of an unrelated mycovirus (12).…”
mentioning
confidence: 99%